Using a Social Network Strategy to Distribute HIV Self-Test Kits to African American and Latino MSM. (1st September 2018) - Lightfoot, Marguerita A.; Campbell, Chadwick K.; Moss, Nicholas; Treves-Kagan, Sarah; Agnew, Emily; Kang Dufour, Mi-Suk; Scott, Hyman; Sa'id, Aria M.; Lippman, Sheri A.
Abstract : Background: Men who have sex with men (MSM) continue to be disproportionately impacted globally by the HIV epidemic. Studies suggest that HIV self-testing (HIVST) is highly acceptable among MSM. Social network strategies to increase testing are effective in reaching MSM, particularly MSM of color, who may not otherwise test. We tested a social network–based strategy to distribute HIVST kits to African American MSM (AAMSM) and Latino MSM (LMSM). Setting: This study was conducted in Alameda County, California, a large, urban/suburban county with an HIV epidemic mirroring the national HIV epidemic. Methods: From January 2016 to March 2017, 30 AAMSM, LMSM, and transgender women were trained as peer recruiters and asked to distribute 5 self-test kits to MSM social network members and support those who test positive in linking to care. Testers completed an online survey after their test. We compared peer-distributed HIVST testing outcomes to outcomes from Alameda County's targeted, community-based HIV testing programs using χ 2 tests. Results: Peer-distributed HIVST to 143 social and sexual network members, of whom 110 completed the online survey. Compared with MSM who used the County's sponsored testing programs, individuals reached through the peer-based self-testing strategy were significantly more likely to have never tested for HIV (3.51% vs. 0.41%, P < 0.01) and to report a positive test result (6.14% vs. 1.49%, P < 0.01). Conclusion: Findings suggest that a network-based strategy for self-test distribution is a promising intervention to increase testing uptake and reduce undiagnosed infections among AAMSM and LMSM.